2019
DOI: 10.1177/0019556119844616
|View full text |Cite
|
Sign up to set email alerts
|

Do Governance Indicators Matter for Economic Growth? The Case of Sri Lanka

Abstract: This study attempts to identify the impact of governance indicators on economic growth using time series data for Sri Lanka from 1996 to 2016 published by the World Bank. The Phillips–Perron (PP) unit root test confirmed that all the variables are integrated in order one and suggested the use of cointegration technique to identify the long-run relationship between the variables. All the lag length selection criteria except Schwarz Information Criterion (SIC) advocated the use of one lag as an optimal lag lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…However, some researchers found some dimensions of WGIs that negatively correlate to educational outcomes and others such as government effectiveness with GDP in South Asian countries, and with higher education enrollment in Latin American and Caribbean counties in the years from 1996-2012 (Zaman, 2016). Vinayagathasan and Ramesh's (2019) study also showed the negative relation between rule of law and GDPPC in the case of Sri Lanka from 1996 to 2016.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, some researchers found some dimensions of WGIs that negatively correlate to educational outcomes and others such as government effectiveness with GDP in South Asian countries, and with higher education enrollment in Latin American and Caribbean counties in the years from 1996-2012 (Zaman, 2016). Vinayagathasan and Ramesh's (2019) study also showed the negative relation between rule of law and GDPPC in the case of Sri Lanka from 1996 to 2016.…”
Section: Discussionmentioning
confidence: 93%
“…While considering the effect of governance on educational performance, it is revealed as a predictor of socio-economic development of a country such as health, education, economy, livelihood of people and so on. However, there is no uniform results, for example, WGIs are found positive impactful factors on development indicators such as education, Gross Domestic Product Per Capita (GDPPC), human development index (Ahmad & Saleem, 2014;Canfield, 2011;Han et al, 2014;Zaman, 2016) whereas some researchers like Vinayagathasan and Ramesh (2019), Zaki (2016), Briguglio (2016), andAbu-Ismail et al (2016) showed the negative correlation between some indicators of WGIs such as voice and accountability, political stability, rule of law or control of corruption, and average year of schooling or GDPPC. The mixed results on the relation between governance and the development indicators indicate it as a debatable issue.…”
Section: Introductionmentioning
confidence: 99%
“…The result demonstrated the tradeoff between the institution and economic growth also the, geography plays a significant role on economic growth. Vinayagathasan and Ramesh (2019) studied the influence of governance indicators on the growth rate of Sri Lanka during 1996–2016. The study has applied three conventional approaches that include test of correlation, scatter plot, and the technique of ordinary least square (OLS).…”
Section: Review Of Literaturementioning
confidence: 99%
“…However, over a period, good governance has become an important component of the growth process and has given rise to national and international debates. There are influential studies by scholars and academicians on the relationship between governance indicators and economic growth (Bhattacharjee & Haldar, 2015; Fayissa & Nsiah, 2013; Huang & Ho, 2017; Mauro, 1995; Sharma & Mitra, 2019; Singh, 2019; Singh & Pradhan, 2020; Vinayagathasan & Ramesh, 2019). BRICS can concentrate on improving institutional quality by reducing corruption and increasing the political transparency that is found to be low in the BRICS economies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation